2015
DOI: 10.17507/jltr.0602.02
|View full text |Cite
|
Sign up to set email alerts
|

Negotiation for Meaning and Feedback among Language Learners

Abstract: Abstract-Negotiation for meaning (NfM) in second language acquisition is defined as an attempt to overcome comprehension problems. This paper addresses a level of NfM: Requests for clarification in terms of communicative intent that are not generated from linguistic problems or communication breakdowns. It also explores reasons for the emergence of this level of NfM from the view of a language user. With particular reference to the meaning of utterances, the paper discusses whether certain inputs are able to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In line with the observation that most MOOCs tend to adopt xMOOC features, such as short videos, automarked quizzes and peer/self-assessment (Glance et al, 2013;Wong, 2015), those for language learning, as illustrated above, are no exception. For language learning, however, it has been suggested that the connectivist model would be more suitable, as learners may participate in the extensive interaction in negotiation for meaning (Cook, 2015) and for practising the different language skills acquired in the courses (de Larreta-Azelain, 2014). The pedagogy features of language MOOCs, as shown in the results of this study, reveal its limitations in providing comprehensive training for learners in all areas of language learning.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the observation that most MOOCs tend to adopt xMOOC features, such as short videos, automarked quizzes and peer/self-assessment (Glance et al, 2013;Wong, 2015), those for language learning, as illustrated above, are no exception. For language learning, however, it has been suggested that the connectivist model would be more suitable, as learners may participate in the extensive interaction in negotiation for meaning (Cook, 2015) and for practising the different language skills acquired in the courses (de Larreta-Azelain, 2014). The pedagogy features of language MOOCs, as shown in the results of this study, reveal its limitations in providing comprehensive training for learners in all areas of language learning.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, it was decided that requests would be limited to what Long (1983) refers to as requests to negotiate meaning. These requests can be used to help learners during communication breakdowns (Cook, 2015) and allow them to assess whether or not they have been successful at communicating with native/proficient speakers (Long, 1983). There are three different types of requests within this category.…”
Section: Linguistic Needs Analysismentioning
confidence: 99%
“…), and comprehension checks, also known as repetition ("You want ____?"). These requests allow the learner to receive additional linguistic information and input and can help prevent communication breakdowns (Cook, 2015). The use of the requests was especially useful for the proficiency level of the target learners as they would allow them to effectively seek assistance in the form of repetition, further explanation, or rewording to ensure understanding (CCLB, 2012).…”
Section: Linguistic Needs Analysismentioning
confidence: 99%
“…"), and comprehension checks, also known as repetition ("You want ____?"). These requests allow for more information and comprehensible input to be obtained and can help prevent communication breakdowns (Cook, 2015). Furthermore, these types are meaning-focused rather than form-focused, aligning with the principles of TBLT.…”
Section: Linguistic Needs Analysismentioning
confidence: 99%
“…To this end, it was decided that requests would be limited to what Long (1983) refers to as requests to negotiate meaning. These requests can be used to help learners during communication breakdowns (Cook, 2015) and allow them to assess whether or not they have been successful at communicating with native/proficient speakers (Long, 1983). There are three different types of requests within this category.…”
Section: Linguistic Needs Analysismentioning
confidence: 99%